Pengolahan Ampas Tahu Menjadi Kripik Rasa Desa Tarokan, Banyuanyar, Jawa Timur - Riski; Maulidi, Slamet; Hidayatullah, M. (Kalam Nusantara Institute, 2024)
Tofu dregs are a by-product of tofu production which still has a relatively high protein content, because not all of the protein can be extracted in the process of making tofu. So far, the utilization of tofu dregs is still limited as animal feed and is processed into tempe gembus. Tofu chips are a new breakthrough for developing the tofu factory business in Tarokan Village, Banyuanyar Regency. This food is processed by utilizing tofu dregs made from soybeans which contain carbohydrates and are rich in protein and fiber so that they are beneficial for the health of the body, from treating diabetes, strengthening bones, and so on. The method we use is qualitative, field observation methods, in-depth interviews, documentation and lab tests. The results and discussion are the preparation of tools and materials, washing, drying, mixing the dough, printing, frying, packaging and branding. The conclusion of this community service program is the innovation of chip products with other additives such as flavors and fragrances. Packaging uses a plastic standing pouch and branding in the form of a front label and a back label containing the product logo, product description. The development of tofu chips can be given a variety of flavors such as spicy, sweet, salty.